2021
DOI: 10.2319/120720-990.1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of bacterial strains in patients undergoing orthodontic treatment with and without fixed appliances

Abstract: Objectives To identify microorganisms isolated from patients wearing fixed orthodontic appliances and to evaluate the resistance of isolated bacterial strains to different antimicrobials. Materials and Methods Seventeen healthy patients wearing a fixed orthodontic appliance (group 1) and six nonwearers (group 2, control group) were evaluated. The biofilm that formed around the orthodontic brackets was collected, and the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…From baseline to one month of ROA therapy, a significant increase (p < 0.001) in the number of Candida albicans counts was observed in saliva 20 and on the oral mucosa. 26 During the early stages of FOA, Hägg et al 14 found a significant Candida increase on the dorsum of the tongue (p < 0.001), but not in saliva and plaque samples. Arslan et al 15 reported an increase in the number of colony-forming units (CFU) was statistically significant (p < 0.001) both in saliva and on tooth surfaces.…”
Section: Short-term (<3 Months) Candida Changesmentioning
confidence: 97%
See 4 more Smart Citations
“…From baseline to one month of ROA therapy, a significant increase (p < 0.001) in the number of Candida albicans counts was observed in saliva 20 and on the oral mucosa. 26 During the early stages of FOA, Hägg et al 14 found a significant Candida increase on the dorsum of the tongue (p < 0.001), but not in saliva and plaque samples. Arslan et al 15 reported an increase in the number of colony-forming units (CFU) was statistically significant (p < 0.001) both in saliva and on tooth surfaces.…”
Section: Short-term (<3 Months) Candida Changesmentioning
confidence: 97%
“…The characteristics of the studies are presented in Table IV. Of the 16 included studies, all were prospective in nature and included four reports which described the changes in Candida in patients treated using a ROA 13,17,20,26 and nine studies which described those treated with FOA. 8,[14][15][16][21][22][23][24]27 Three studies analysed and compared treated and non-treated patients, two of which involved a ROA 17,18 and one used FOA 25 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations